2014
DOI: 10.11646/zootaxa.3847.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of the semi-aquatic skink Parvoscincus leucospilos (Reptilia: Squamata: Scincidae), with description of three new species

Abstract: We review the recent discovery of multiple populations of the enigmatic, semi-aquatic Sphenomorphus Group skink, Parvoscincus leucospilos Peters, and investigate the morphological and genetic diversity of isolated, allopatric populations of this unique skink. Our investigations support the recognition of four unique evolutionary lineages distributed across Luzon Island in the Philippines, three of which are herein described as new species (P. tikbalangi sp. nov., P. manananggalae sp. nov., and P. duwendorum sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Parvoscincus kitangladensis is most closely related to the miniature Luzon forest species (e.g., Parvoscincus lawtoni , and possibly Parvoscincus luzonensis ) but is phenotypically similar to members of the Parvoscincus decipiens complex and other small bodied taxa from Luzon (i.e. Parvoscincus laterimaculatus , Parvoscincus leucospilos ; Linkem et al 2011; Siler et al 2014e) and even Palawan (e.g., Insulasaurus victoria , Insulasaurus traanorum ; Linkem et al 2010a, 2011). Considered “Least Concern” (LC; IUCN 2010, 2016), this species is reasonably widespread but remains poorly understood in microhabitat preferences.…”
Section: Species Accountsmentioning
confidence: 96%
“…Parvoscincus kitangladensis is most closely related to the miniature Luzon forest species (e.g., Parvoscincus lawtoni , and possibly Parvoscincus luzonensis ) but is phenotypically similar to members of the Parvoscincus decipiens complex and other small bodied taxa from Luzon (i.e. Parvoscincus laterimaculatus , Parvoscincus leucospilos ; Linkem et al 2011; Siler et al 2014e) and even Palawan (e.g., Insulasaurus victoria , Insulasaurus traanorum ; Linkem et al 2010a, 2011). Considered “Least Concern” (LC; IUCN 2010, 2016), this species is reasonably widespread but remains poorly understood in microhabitat preferences.…”
Section: Species Accountsmentioning
confidence: 96%
“…B. bicolor, O. cumingi and Parvoscincus leucospilos showed major elevational range extensions. Siler et al (2014) reported that P. leucospilos is common at elevations from 200–800 m a.s.l. ; our specimen was collected at 1,150 m a.s.l.…”
Section: Resultsmentioning
confidence: 99%
“…a Observed for two individuals. (Siler et al 2011b(Siler et al , 2012a(Siler et al , 2014Davis et al 2014).…”
Section: Phylogenetic Relationships and Genetic Divergencementioning
confidence: 99%